On the disintegration of Molluginaceae: a new genus and family (Kewa, Kewaceae) segregated from Hypertelis, and placement of Macarthuria in Macarthuriaceae - Christenhusz, Maarten J.m.; Brockington, Samuel F.; Christin, Pascal-Antoine; Sage, Rowan F. (Phytotaxa, 2014)
Molecular studies have shown that Molluginaceae in the traditional sense is polyphyletic. Several genera have already been separated into various families (e.g. Caryophyllaceae, Limeaceae, Lophiocarpaceae, Microteaceae), but recent studies have shown that Macarthuria and Hypertelis also make Molluginaceae polyphyletic if they remain to be included in this family. Hypertelis is biphyletic, with its type species found to belong to Molluginaceae sensu stricto, but the remainder of the genus is to be placed elsewhere. Therefore a new genus, Kewa, is proposed for the rest of Hypertelis, and two new family names are coined: Kewaceae and Macarthuriaceae, which are here morphologically characterized.